SIMULATION & DESIGN OF POWER FACTOR CORRECTION PROTOTYPE FOR BLDC MOTOR CONTROL - Pradeep Kumar; P.R. Sharma; Ashok Kumar (European Scientific Journal, ESJ, 2013)
This paper presents a design, development and simulation of a controller prototype for Power Factor Correction circuit applied to BLDC Motor Control. A laboratory prototype model of the Power Factor Correction circuit is designed and fabricated. Mathematical modelling and simulation of the power factor correction circuit are implemented on the MATLAB Simulink. The control algorithm is implemented on a 16 bit microcontroller dsPIC33FJ32MC204 from Microchip. Experimental results thus obtained on the prototype are also reported in the paper.